Nutritional Ketosis as a Potential Treatment for Alcohol Use Disorder - Mahajan, Vikrant R.; Elvig, Sophie K.; Vendruscolo, Leandro F.; Koob, George F.; Darcey, Valerie L.; King, M. Todd; Kranzler, Henry R.; Volkow, Nora D.; Wiers, Corinde E. (Frontiers in Psychiatry, 2021)
Alcohol use disorder (AUD) is a chronic, relapsing brain disorder, characterized by compulsive alcohol seeking and disrupted brain function. In individuals with AUD, abstinence from alcohol often precipitates withdrawal symptoms than can be life threatening. Here, we review evidence for nutritional ketosis as a potential means to reduce withdrawal and alcohol craving. We also review the underlying mechanisms of action of ketosis. Several findings suggest that during alcohol intoxication there is a shift from glucose to acetate metabolism that is enhanced in individuals with AUD. During withdrawal, there is a decline in acetate levels that can result in an energy deficit and could contribute to neurotoxicity. A ketogenic diet or ingestion of a ketone ester elevates ketone bodies (acetoacetate, β-hydroxybutyrate and acetone) in plasma and brain, resulting in nutritional ketosis. These effects have been shown to reduce alcohol withdrawal symptoms, alcohol craving, and alcohol consumption in both preclinical and clinical studies. Thus, nutritional ketosis may represent a unique treatment option for AUD: namely, a nutritional intervention that could be used alone or to augment the effects of medications.